2020
DOI: 10.1108/jd-06-2020-0104
|View full text |Cite
|
Sign up to set email alerts
|

Social aspects of personal information organization

Abstract: PurposeThe purpose of this paper is to examine how individuals' personal information organization reflects their social environments in order to understand social aspects of personal information organization.Design/methodology/approachBy using a cognitive sociological approach and based on the personal information organization process (PIOP) model (Oh, 2019), this study investigates the social aspects of personal information organization by analyzing the pre-diary interview, a diary, and two post-diary intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Bergman et al (2019) tested and quantified the effect of factors related to collection size, file properties and workload on file retrieval. Oh’s (2020) study examined how individuals’ personal information organization reflected their social environments in order to understand social aspects of personal information organization. Further evidence of PIM research during this period is that researchers were beginning to search for a suitable theoretical basis for PIM research.…”
Section: Discussionmentioning
confidence: 99%
“…Bergman et al (2019) tested and quantified the effect of factors related to collection size, file properties and workload on file retrieval. Oh’s (2020) study examined how individuals’ personal information organization reflected their social environments in order to understand social aspects of personal information organization. Further evidence of PIM research during this period is that researchers were beginning to search for a suitable theoretical basis for PIM research.…”
Section: Discussionmentioning
confidence: 99%
“…, 2004; Kaye et al. , 2006; Oh, 2021). These contexts are very different from those of marginalised communities in developing countries, for whom the lack of information, rather than the abundance of information, is a problem, and access to technology is limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Oh (2021, p. 558) has argued, “the way individuals organize their personal information often reflects their social environment”; yet, the social aspects that impact on how they organise their personal information organisation have rarely been studied. Little is known about the ways rural communities in developing countries preserve information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existing studies on personal information management have identified strategies for and patterns of organising and maintaining personal information (Jones et al, 2017), with particular attention given to specific context, content or activity (for example, academic (Oh, 2021), file management (Dinneen and Julien, 2019), web bookmarks (Bergman et al, 2021)). However, little is known about these strategies and patterns in the migration context.…”
Section: Personal Information Management Practicesmentioning
confidence: 99%